Development, deprivation and welfare policy : essays in honour of Prof. Baidyanath Misra - Mallik, Radhamohan; Mallik, Radhamohan; Misra, Baidyanath (Rawat Publications, 2005)
Baidyanath Misra, b. 1920, Indian economist; contributed articles.